Hashimoto’s Thyroiditis and Papillary Thyroid Carcinoma: A Follow-Up Study in Patients with Absence of Aggressive Risk Factors at the Surgery of the Primary Tumor - Andrea Marongiu; Susanna Nuvoli; Andrea De Vito; Sonia Vargiu; Angela Spanu; Giuseppe Madeddu (Diagnostics, 2023)
Hashimoto’s thyroiditis (HT) is often associated with papillary thyroid carcinoma (PC); it is still a matter of controversy whether the behavior of carcinoma is more aggressive or not. During the follow-up, we retrospectively enrolled 97 patients with PC/HT after thyroidectomy without risk factors at the surgery of the primary tumor, such as multifocality/multicentricity, extrathyroid tumor extension, vascular invasion, neck and distant metastases, and aggressive histological variants. HT diagnosis was confirmed by histology and serum thyroid antibodies. Tumor size was ≤10 mm in 64 cases (microcarcinomas); 206 matched PC patients after thyroidectomy without HT and risk factors were enrolled as controls, totaling 122 microcarcinomas. During follow-up, metastases occurred in 15/97 (15.5%) PC/HT cases, eight microcarcinomas, and in 16/206 (7.8%) without HT, eight microcarcinomas (p = 0.04). Considering both PC/HT and PC patients without HT who developed metastases, univariate analysis showed an increased risk of metastases in patients with HT coexistence, OR: 2.17 (95% CI 1.03–4.60) p = 0.043. Disease-free survival (DFS) was significantly (p = 0.0253) shorter in PC/HT than in the controls. The present study seems to demonstrate that HT is not a cancer protective factor in PC patients given the less favorable outcomes and significantly shorter DFS. HT may also represent an independent recurrence predictor without other risk factors.